Sistem Pendukung Keputusan Penilaian Kinerja Guru Menggunakan Metode Simple Additive Weighting (SAW) - Suciana Rahayu; Anita Sindar Sinaga (PRPM STMIK TRIGUNA DHARMA, 2022)
It is very important to evaluate teacher performance regularly to improve the quality of teacher human resources. SMK 1 Negeri Labu conducts teacher performance assessments every 3 months but the mechanism is less effective due to lack of transparency. The SAW method is part of the DSS used to help determine decisions based on alternative data and criteria data. Data processing is implemented according to the calculation of the SAW method to determine the decision matrix and then make a ranking of the total alternative data. In this study there were 20 teachers who were assessed with 9 assessment criteria, the ranking results showed that alternative data A03 obtained the highest score, it was decided that A03 had the best teacher performance. The design of the system developed with UML resulted in a teacher performance appraisal system. This study aims to help the school determine the best teacher performance systematically processed by the system. Suggestions from the implementation of this study in order to improve the accuracy of the calculation results, it is recommended to compare the results with other DSS-based methods.